The application of ultrasound-guided cannulated screw removal after proximal tibial fracture surgery: a retrospective study - Gu, Kai; Qin, Jiaqiang; Guo, Meizhen; Chu, Ruiliang; Chen, Jiaxu; Qian, Fusheng; Zhong, Yi (Frontiers in Pediatrics, 2025)
IntroductionCannulated screws are widely used in pediatric orthopedic fixation. However, traditional screw removal requires preoperative x-ray positioning, leading to exposure to ionizing radiation. Sometimes, a larger incision is required, and trauma is a significant cause of x-ray positioning, which cannot be accurately marked on the skin. In this study, we aimed to evaluate the practicability of rapid removal of cannulated screws through a guide needle and small incision using ultrasound (US) guidance to locate the position of the screws accurately.MethodsA retrospective analysis was performed on patients who underwent removal of internal fixation after proximal tibial fracture surgery at our hospital between January 2019 and March 2024. Patients were divided into Group A and Group B based on the different cannulated screw removal techniques. In Group A, the cannulated screws were removed under US guidance, while in Group B, they were removed under direct visualization using a traditional incision. The operative time, blood loss, success rate of removal, radiation frequency, and incision length were statistically analyzed. Knee function was evaluated using the Knee Society Score.Results53 patients aged 15.3 ± 0.1 years were included in this study. Group A showed 50% shorter incision length (1.5 vs. 3.0 cm, p = 0.005) and average screw incisions (0.5 vs. 1.0 cm, p = 0.007), along with complete elimination of preoperative radiation exposure (0 vs. 2 times, p < 0.001) and dose (0 vs. 0.102 mGy, p < 0.001) compared to Group B. Participants in Group A had no postoperative complications, whereas one patient in Group B had an incision infection; however, no significant difference was observed between the groups.DiscussionUS-guided cannulated screw removal can be used in children with proximal tibial fractures, significantly reducing the preoperative radiation time and dose while minimizing the incisional length.Level of evidenceIII